2017
DOI: 10.1038/s41467-017-01965-8
|View full text |Cite
|
Sign up to set email alerts
|

HIF drives lipid deposition and cancer in ccRCC via repression of fatty acid metabolism

Abstract: Clear cell renal cell carcinoma (ccRCC) is histologically defined by its lipid and glycogen-rich cytoplasmic deposits. Alterations in the VHL tumor suppressor stabilizing the hypoxia-inducible factors (HIFs) are the most prevalent molecular features of clear cell tumors. The significance of lipid deposition remains undefined. We describe the mechanism of lipid deposition in ccRCC by identifying the rate-limiting component of mitochondrial fatty acid transport, carnitine palmitoyltransferase 1A (CPT1A), as a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
287
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(307 citation statements)
references
References 43 publications
19
287
1
Order By: Relevance
“…41 HIF-2α controls the fate of fatty acids either in phospholipid synthesis or in storage to form lipid droplets. 42 We observed elevated levels of PGs and PIs and suppressed aminophospholipids such as PSs and PEs. PEs are synthesized in mitochondria and are produced from the decarboxylation of PS synthesized in endoplasmic reticulum (ER).…”
Section: Discussionmentioning
confidence: 65%
“…41 HIF-2α controls the fate of fatty acids either in phospholipid synthesis or in storage to form lipid droplets. 42 We observed elevated levels of PGs and PIs and suppressed aminophospholipids such as PSs and PEs. PEs are synthesized in mitochondria and are produced from the decarboxylation of PS synthesized in endoplasmic reticulum (ER).…”
Section: Discussionmentioning
confidence: 65%
“…Transcriptional repression of carnitine palmitoyltransferase ( CPT1A ), the rate limiting enzyme involved in fatty acid transport into the mitochondria for beta-oxidation, also occurs in ccRCC via a HIF-α dependent mechanism [80]. A recent report found that pVHL reconstitution in several ccRCC cell lines reduced lipid droplet (LD) accumulation in a CPT1A dependent manner (i.e., knockdown of CPT1A in pVHL-reconstituted cells partially increased lipid accumulation).…”
Section: Metabolic Reprogramming In Ccrccmentioning
confidence: 99%
“…These metabolic changes were also correlated with gene expression levels of lipogenic genes. While it is clear that suppression of either HIF-1α or HIF-2α markedly reduces LD formation in ccRCC [96], [34], [80], the target genes and mechanisms responsible for the clear cell phenotype have not been completely defined. Additionally, the role of other lipogenic transcription factors such as sterol regulatory element-binding protein 1 or 2 (SREBP1/2), PPARγ, and carbohydrate-responsive element-binding protein (ChREBP) remain to be fully elucidated in ccRCC.…”
Section: Metabolic Reprogramming In Ccrccmentioning
confidence: 99%
“…Similar to other solid tumors, ccRCC is primarily driven by loss of key tumor suppressor such as von Hippel-Lindau (VHL) and activation of oncogenes (23)(24)(25). Closely associated with these genetic alterations, lipid metabolic processes are dramatically altered in the ccRCC tumor microenvironment (3,4,(26)(27)(28)(29)(30)(31)(32)(33). In fact, the "clear cell" subtype gets its name from cholesterol ester-rich lipid droplets that accumulate in tumor cells (32,33).…”
Section: Discussionmentioning
confidence: 99%